Reduction of α-galactooligosaccharides in soyamilk by Lactobacillus fermentum CRL 722: In vitro and in vivo evaluation of fermented soyamilk - Leblanc, Jean Guy Joseph (2004)
Aims: Consumption of soya-derived products has been hampered by the presence of α-galactooligosaccharides (α-GOS) because mammals lack pancreatic α-galactosidase (α-Gal) which is necessary for their hydrolysis. These sugars thus reach the large intestine causing gastrointestinal disorders in sensitive individuals. The use of lactic acid bacteria (LAB) expressing α-Gal is a promising solution for the degradation of α-GOS in soyamilk. Methods and Results: The capacity of the LAB Lactobacillus fermentum CRL 722 to properly degrade α-GOS was studied in vitro using controlled fermentation conditions and in vivo using a rat model. Lactobacillus fermentum CRL 722 was able to grow on commercial soyamilk and completely eliminated stachyose and raffinose during fermentation because of its high α-Gal activity. Rats fed soyamilk fermented by this LAB had smaller caecums compared with rats fed unfermented soyamilk. Conclusions: Soyamilk fermentation by Lact. fermentum CRL 722 results in the reduction of α-GOS concentrations in soyamilk, thus eliminating possible undesirable physiological effects normally associated with its consumption. Significance and Impact of the Study: Fermentation with Lact. fermentum CRL 722 could prevent gastrointestinal disorders in sensitive individuals normally associated with the consumption of soya-based products. This LAB could thus be used in the elaboration of novel fermented vegetable products which better suit the digestive capacities of consumers.